Phenomenal, Normative, and Other Explanatory Gaps: A General Diagnosis. (20th October 2017) - Mehta, Neil
Abstract : I assume that there exists a general phenomenon, the phenomenon of theexplanatory gap, that surrounds consciousness, normativity, intentionality, and more. Explanatory gaps are often thought to foreclose reductive possibilities wherever they appear. In response, reductivists who grant the existence of these gaps have offered countless local solutions. But typically such reductivist responses have a serious shortcoming: because they appeal to essentially domain‐specific features, they are impossible to fully generalize. Here I do better. Taking for granted that the explanatory gap is a genuine phenomenon, I offer a fully general diagnosis that unifies these previously fragmented reductivist responses.